Outcomes of amniocentesis at a tertiary maternal-fetal medicine unit in Malaysia: a five-year retrospective cohort study of cytogenetic yield and procedure-related complications - Naidu, Shashi Indran; Lee, Jes Sie; Tan, Gillian Yi Zhen; Balan, Yuvintherr Jeyah; Lim, Joanne Xu Mei; M. Nor, Nurul Huda; Santharaguru, Shaarmini; Juliana, Kamarudin; Kumar, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Amniocentesis is the most widely performed invasive prenatal diagnostic procedure worldwide. While its diagnostic accuracy is well established, procedure-related risks such as miscarriage and preterm prelabour rupture of membranes (PPROM) remain central to patient counselling. Although international safety and diagnostic outcome data are robust, regional evidence from Southeast Asia is limited. This study aimed to evaluate the cytogenetic yield and short-term complications of amniocentesis performed in a Malaysian tertiary maternal-fetal medicine (MFM) training centre over a five-year period. Methods: A retrospective cohort study was conducted, including all women who underwent amniocentesis at hospital Tuanku Jaafar (HTJ), Seremban, between January 2018 and December 2022. Maternal demographics, ethnicity, indications, cytogenetic outcomes, and procedure-related complications within 14 days were extracted from hospital records. Descriptive statistics were used to summarise baseline characteristics and outcomes. Associations were analysed using Fisher’s exact test, and binary logistic regression was performed to identify independent predictors of miscarriage and PPROM. Results: A total of 650 amniocentesis were included. Most women were <35 years (34.8%) or 38-40 years (31.1%); the majority were Malay (73.8%). Advanced maternal age was the leading indication (54.6%). Cytogenetic analysis revealed normal results in 90.9% of cases. Abnormal findings included trisomy 21 (1.7%), trisomy 18 (3.4%), trisomy 13 (0.8%), and other aneuploidies (3.1%), yielding an overall abnormal karyotype rate of 8.9%. Procedure-related complications were rare, with miscarriage in 0.3% (n=2) and PPROM in 0.6% (n=4). An abnormal karyotype was significantly associated with miscarriage and PPROM in univariate analysis (p<0.001) and remained an independent predictor of PPROM on logistic regression (OR=2.74, 95% CI=1.5-5.1, p=0.001). No independent predictors of miscarriage were identified. Conclusions: Amniocentesis in this tertiary MFM training centre was associated with a high diagnostic yield and very low short-term complication rates, consistent with international benchmarks. The clustering of complications among abnormal karyotypes suggests that biological vulnerability contributes to adverse outcomes independent of procedural factors. These findings reinforce the safety of amniocentesis in the hands of experienced practitioners and provide important regional data for patient counselling and training.